2005
DOI: 10.1002/adfm.200400521
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Structural and Optical Properties of Composite Polymer/Fullerene Films for Organic Solar Cells

Abstract: We investigate thin poly(3‐hexylthiophene‐2,5‐diyl)/[6,6]‐phenyl C61 butyric acid methyl ester (P3HT/PCBM) films, which are widely used as active layers in plastic solar cells. Their structural properties are studied by grazing‐incidence X‐ray diffraction (XRD). The size and the orientation of crystalline P3HT nanodomains within the films are determined. PCBM crystallites are not detected in thin films by XRD. Upon annealing, the P3HT crystallinity increases, leading to an increase in the optical absorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

47
674
5
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 813 publications
(729 citation statements)
references
References 12 publications
(10 reference statements)
47
674
5
3
Order By: Relevance
“…The growth of the PCBM clusters leads to the formation of percolation paths and, therefore, improvement of the photocurrent. Further studies by Erb et al 51 suggest that the significant increase in optical absorption is due to the aggregation state of P3HT, from amorphous (non-annealed) to crystalline (annealed). Grazing-incidence X-ray diffraction (XRD) measurements of P3HT:PCBM films reveal an increase in sharpness of the diffraction peak pertaining to the interchain, intra-lamellar ordering (a-axis) of P3HT upon thermal annealing Q4 ( Fig.…”
Section: Thermal Annealingmentioning
confidence: 97%
See 2 more Smart Citations
“…The growth of the PCBM clusters leads to the formation of percolation paths and, therefore, improvement of the photocurrent. Further studies by Erb et al 51 suggest that the significant increase in optical absorption is due to the aggregation state of P3HT, from amorphous (non-annealed) to crystalline (annealed). Grazing-incidence X-ray diffraction (XRD) measurements of P3HT:PCBM films reveal an increase in sharpness of the diffraction peak pertaining to the interchain, intra-lamellar ordering (a-axis) of P3HT upon thermal annealing Q4 ( Fig.…”
Section: Thermal Annealingmentioning
confidence: 97%
“…A substantial improvement in the PCE of P3HT:PCBM based solar cells has been obtained by thermal annealing at around 140 1C, and the favourable influence of annealing on blend film microstructure and solar cell performance is well documented. [50][51][52][53] The mechanism by which current density and PCE increase upon thermal annealing in P3HT:PCBM is not known precisely but it is believed to involve increased optical absorption and improved charge transport, both due to polymer crystallization, as well as improved charge pair separation efficiency, due to optimized phase segregation. Some of the literature is reviewed below.…”
Section: Thermal Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…When represented by a two-dimensional model, it showed that a phase separated morphology with feature sizes smaller than ~50 nm could improve charge transport within and between the two phases and reduce bimolecular charge recombination [6]. In the case of P3HT/PCBM, the molecular ordering of rr-P3HT is concerned with photon absorption and hole transport [7][8][9], and the suitable size of phase separation is related to charge separation. In order to achieve an optimum morphology, many methods have been employed, including thermal annealing [10,11], solvent vapor annealing [12][13][14], mixed solvent [15,16], introduction of additives [17,18] and so on.…”
mentioning
confidence: 99%
“…The scale of them was obviously much greater than the exciton diffusion length. Meanwhile, the diffusion of PCBM out of the polymer matrix to form aggregates enables the disordered P3HT to further crystallize [7], not disrupts the ordered lamellar …”
mentioning
confidence: 99%